Competition between audiovisual correspondences aids understanding of interactions between auditory and visual perception - Getz, Laura Marie (Frontiers in Cognition, 2023)
An audiovisual correspondence (AVC) refers to an observer's seemingly arbitrary yet consistent matching of sensory features across the two modalities; for example, between auditory pitch height and visual height or visual size. Research on AVCs frequently uses a speeded classification procedure in which participants are asked to rapidly classify the pitch of a sound accompanied either by a congruent or an incongruent visual object (e.g., high pitches are congruent with higher/smaller visual objects and incongruent with lower/larger visual objects). To investigate the strength of these pitch AVCs (height, size, spatial frequency, brightness, sharpness), trials where the height AVC competed with each other AVC in terms of pitch congruency were created. For example, when classifying pitch height, participants were presented with trials where both visual height and size were congruent or incongruent with pitch; additionally, there were trials where height was congruent but size was incongruent (i.e., high pitch matched with large object at high height) and trials where size was congruent but height was incongruent (i.e., high pitch matched with small object at low height). Based on previous work, congruency between pitch and height was expected to be more important than congruency between pitch and spatial frequency, brightness, sharpness, or size. As predicted, in all four studies, RTs when only height was congruent were just as fast as when both dimensions were congruent. In contrast, RTs when only spatial frequency, brightness, sharpness, or size was congruent (and height was incongruent) were just as slow as when both dimensions were incongruent. These results reinforce the superiority of the pitch-height AVC and can be interpreted based on the metaphor used for pitch in English, showing the importance of semantic/linguistic effects to understanding AVCs.